Effects of Kiwifruit Consumption on Blood Pressure in Adults: A Systematic Review and Meta‐Analysis - Shirin Ghotboddin Mohammadi; Neda Haghighat; Azadeh Dehghani; Mohammad Mahdi Rafiei; Pedram Pam; Mohammadreza Amirkhan‐Dehkordi; Mohammad Ali Goudarzi; Omid Asbaghi; Moslem Naderian; Ali Hosseini; Mehdi Karimi (Health Science Reports, 2026)
ABSTRACT Background Hypertension represents a major public health challenge worldwide. Nutritional strategies, particularly increased fruit consumption, are being explored as non‐pharmacological means of regulating blood pressure (BP). Kiwifruit, a fruit high in potassium and antioxidant compounds, has been proposed to exert antihypertensive effects; however, findings from individual studies have been inconclusive. Aim This meta‐analysis assesses the impact of kiwifruit consumption on BP in adults. Method A comprehensive search of online databases was conducted up to May 2026 to identify relevant randomized controlled trials (RCTs). Pooled effect sizes were calculated as weighted mean differences (WMDs) with 95% confidence intervals (CIs) using a random‐effects model to account for between‐study variability. Result The pooled analysis of six RCTs (comprising 10 intervention arms) indicated that the consumption of kiwifruits led to a significant reduction in both systolic BP (WMD: −5.73 mmHg, 95%CI: −9.02 to −2.44, p = 0.001) and diastolic BP (WMD: −4.08 mmHg, 95%CI: −6.07 to −2.10, p < 0.001). Subgroup analysis showed that kiwifruit consumption significantly reduced BP, particularly among individuals with normal BMI, those receiving higher doses (3/day), and male participants. The effect was more pronounced for those with elevated baseline BP and in shorter trials (≤ 8 weeks). Significant differences were observed between subgroups in terms of dose and BMI. Conclusion Kiwifruit consumption may contribute to BP reduction as a dietary intervention, particularly among individuals with elevated blood pressure and normal BMI. However, these findings should be interpreted with caution due to the limited number of available RCTs and require confirmation in larger, well‐designed studies.